Measurement of Low‐Density Lipoprotein Cholesterol Levels in Primary and Secondary Prevention Patients: Insights From the PALM Registry - Angela M. Lowenstern; Shuang Li; Ann Marie Navar; Veronique L. Roger; Jennifer G. Robinson; Anne C. Goldberg; Salim S. Virani; L. Veronica Lee; Peter W. F. Wilson; Michael J. Louie; Eric D. Peterson; Tracy Y. Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The 2013 American College of Cardiology/American Heart Association Guideline on the Treatment of Blood Cholesterol to Reduce Atherosclerotic Cardiovascular Risk in Adults recommended testing low‐density lipoprotein cholesterol (LDL‐C) to identify untreated patients with LDL‐C ≥190 mg/dL, assess lipid‐lowering therapy adherence, and consider nonstatin therapy. We sought to determine whether clinician lipid testing practices were consistent with these guidelines. Methods and Results The PALM (Patient and Provider Assessment of Lipid Management) registry enrolled primary and secondary prevention patients from 140 US cardiology, endocrinology, and primary care offices in 2015 and captured demographic data, lipid treatment history, and the highest LDL‐C level in the past 2 years. Core laboratory lipid levels were drawn at enrollment. Among 7627 patients, 2787 (36.5%) had no LDL‐C levels measured in the 2 years before enrollment. Patients without chart‐documented LDL‐C levels were more often women, nonwhite, uninsured, and non–college graduates (all P<0.01). Patients without prior lipid testing were less likely to receive statin treatment (72.6% versus 76.0%; P=0.0034), a high‐intensity statin (21.5% versus 24.3%; P=0.016), nonstatin lipid‐lowering therapy (24.8% versus 27.3%; P=0.037), and had higher core laboratory LDL‐C levels at enrollment (median 97 versus 92 mg/dL; P<0.0001) than patients with prior LDL‐C testing. Of 166 individuals with core laboratory LDL‐C levels ≥190 mg/dL, 36.1% had no LDL‐C measurement in the prior 2 years, and 57.2% were not on a statin at the time of enrollment. Conclusions In routine clinical practice, LDL‐C testing is associated with higher‐intensity lipid‐lowering treatment and lower achieved LDL‐C levels.